Epidemiological and geographical characterization of leprosy in a Brazilian hyperendemic municipality - Soares Camargo Marciano, Lucia Helena; Fernandes Belone, Andrea de Faria; Rosa, Patricia Sammarco; Broch Coelho, Neusa Maria; Ghidella, Cassio Cesar; Tonelli Nardi, Susilene Maria; Miranda, William Cabral; Barrozo, Ligia Vizeu; Lastoria, Joel Carlos [UNESP] (Cadernos Saude Publica, 2018)
This study aimed to identify the distribution pattern of leprosy in a hyperendemic municipality in Brazil and determine its relationship with the clinicoe-pidemiological situation over 11 years. The geographic information .system, MapInfo, spatial scan statistics and the Moran I index were used to analyze new cases. The digital cartographic base was used to map clusters of new paucibacillary and multi bacillary cases and cases in minors under 15 years old. Socioeconomic indicators are shown using the choropleth mapping technique. A reduction in the detection coefficient, increases in high-risk spatial clusters, marked changes in the distribution of high-risk and low-risk clusters, and high-risk clusters of minors under 15 years old were observed from 2006 to 2010, showing recent illness, the presence of active foci, and overlapping of high-risk clusters of multibacillary infection in minors under 15 years old. Leprosy remains a public health problem in Rondonopolis, Mato Grosso State; the high-risk areas require an intensification of control measures and active search strategies to detect new cases.
Keywords: Spatial Analysis; Geographic Information Systems; Epidemiologic Factors